An exploratory study of student-teachers' attitudes, frequencies and obstacles in the use of ICT in teaching English during practicum / Muhamad Anas Sharom - Sharom, Muhamad Anas (Faculty of Education, 2011)
This study was designed to investigate student-teachers usage of ICT in teaching during practicum. Besides, it is also intended to study student-teachers’ attitude towards the integration of ICT in teaching English, as well as the differences between gender towards the attitudes and level of usage in the incorporation of ICT in teaching. Obstacles in using ICT in teaching English were also investigated in this study. A sample of 40 UiTM Section 17 Shah Alam TESL student-teachers participated in this study. Data was collected through survey and analyzed by means of frequency counts and percentages. The analysis revealed that although student-teachers have positive attitudes towards the use of ICT in teaching English, the actual usage of ICT in teaching English is still at low level. Besides, male and female student-teachers have similar attitudes towards the use of ICT in teaching English. In addition, lack of technical support when things went wrong was identified as the main obstacle in integrating ICT in teaching.